1993
DOI: 10.1021/ja00075a066
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium(III) texaphyrin: a novel MRI contrast agent

Abstract: Magnetic resonance imaging (MRI) is now well established as an important tool for the diagnosis and evaluation of a variety of diseases.* 1 2345Nonetheless, considerable effort continues to be devoted to the development and study of potential MRI contrast

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 1 publication
0
66
0
Order By: Relevance
“…We have developed a new radiation sensitizer [i.e., gadolinium(III) texaphyrin (Gd-tex2+)] that, due to its novel mechanism of action, and tumor-selective localizing ability, meets these criteria. An additional benefit of this radiation sensitizer that has not been available with previous sensitizers is that it is detectable in vivo by magnetic resonance imaging (MRI) methods (24,25). Monitoring the selective accumulation of gadolinium(III) texaphyrin in neoplasms by MRI enables the possibility of treatment planning and subsequent monitoring of the response I 2 of cancers to the radiation therapy.…”
mentioning
confidence: 99%
“…We have developed a new radiation sensitizer [i.e., gadolinium(III) texaphyrin (Gd-tex2+)] that, due to its novel mechanism of action, and tumor-selective localizing ability, meets these criteria. An additional benefit of this radiation sensitizer that has not been available with previous sensitizers is that it is detectable in vivo by magnetic resonance imaging (MRI) methods (24,25). Monitoring the selective accumulation of gadolinium(III) texaphyrin in neoplasms by MRI enables the possibility of treatment planning and subsequent monitoring of the response I 2 of cancers to the radiation therapy.…”
mentioning
confidence: 99%
“…The antimicrobial study showed that Ni(II) have more antibacterial activity than other two complexes. Anti cancerous study shows that when of [NiL(NO 3 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of H -C = N-group is indicated by the singlet at δ = 7.023ppm. The multiplet at δ 6.537 ppm -δ = 6.639 ppm and δ = 5.168 ppm -δ = 5.691 ppm were due to the olifinic protons of the side chain and -O-CH 2 -group of the ligand respectively [21][22] . Figure 13), the presence of H -C = N-group is indicated by the singlet at δ = 7.250 ppm it is due to the olifinic protons of the side chain and -O-CH 2 -group.…”
Section: Hnmr Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed donor Schiff bases have been used extensively in catalysis. The design and synthesis of macrocyclic lanthanide complexes is currently attracting considerable attention since they can be used as supramolecular devices and sensors, 1,2 contrast agents in magnetic resonance imaging, [3][4][5] potential radiopharmaceuticals, 6 as possible bioinorganic models for the active sites in metallobiomolecules, 7,8 as synthetic nucleases for in vivo application. 9 The chemistry of macrocyclic complexes has attracted the interest of both inorganic and bioinorganic chemists in recent years.…”
Section: Introductionmentioning
confidence: 99%